The Preliminary Study about Physico-Chemical Property of Bio-Enzyme Produced from Orange Fruits Waste Treated with Different Concentrations of Probiotic - Andri Kurniawan; Diah Mustikasari; Ardiansyah Kurniawan; Muntoro Muntoro; Jhodi Setiadi; Nur Afifah Kholishah (School of Postgraduate Studies, Diponegoro Univer, 2024)
Fruit wastes are reported as among the main contributors to the food waste production. They have impact on the environment so they need to be treated. To reduce the negative effects, fruit wastes must be treated before they are released into environment. Meanwhile, the fruit wastes have been reported about their functional properties and nutritional as bio-enzyme. This preliminary study aimed to provide information about the physico-chemical characteristics of bio-enzyme, including pH, dissolved oxygen (DO), total dissolved solids (TDS), color, and smell of bio-enzyme from orange fruit wastes treated different concentrations of probiotic in anaerobic fermentation. Bio-enzyme was a fermented solution made from a mixture of 15 g brown sugar : 5 kg orange fruit waste : 12 L water. We designed treatments of bio-enzyme fermentation with addition of probiotic, namely 0 ml (control), 80 ml (P1), 160 ml (P2), 240 ml (P3), and 320 ml (P4) for each closed plastic drums 25 L in volume and then were fermented for 35 days. The preliminary study resulted that efficiency of brown sugar and effectivity of fruit waste to produced bio-enzyme with pH 3.4-3.6, TDS 982.7-1152.5 ppm, DO 1.4-2.2 ppm, N total 0.017-0.035%, P 0.017-0.02%, K -.046-0.056%, C organic 0.782-0.936%, C/N ratio 28.29-47.36, reduction sugar 0.005-0.134%, total plate number 4.9 x 104 to 1.1 x 105 colony/g, mold & yeast 2.2 x 104 to 5.8 x 104, light brown of liquid color, little sour to sour and freshness in odor, fungi covered surface of the liquid, Si 12.93-22.53%, Al 1.96-2.39%, Ca 3670-6940 ppm, and Fe 214-806 ppm. This research continues for up to 3 months to determine the metagenome diversity of anaerobic microorganism in bio-enzyme fermentation, characteristics of enzyme, reducing sugar production, and chemical properties of bio-enzyme from orange fruit wastes.